If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = -4 + x Solving 8 = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8 + -1x = -4 + x + -1x Combine like terms: x + -1x = 0 8 + -1x = -4 + 0 8 + -1x = -4 Add '-8' to each side of the equation. 8 + -8 + -1x = -4 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = -4 + -8 -1x = -4 + -8 Combine like terms: -4 + -8 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 5x/2=3x-10 | | 3(5x+2)-5x=2(5x-4) | | x-5=-115*2 | | 25b^2-20b= | | 3*(x+40)-5=x*2 | | 9xyz-(14xyz+7xyz+5z)= | | 3(r-2)-r+4=2r+6 | | 2(x-4)+0.5(2+8x)= | | 4m+5(m-3)=3(2m)+100 | | 825=3c | | w/5.2=16 | | (4/7)(x-4)+(5/6)=(1/6)(x+1) | | 3a^2+9= | | 8x+18x=128 | | (11/7)x-(4/5)=(5x+1/2) | | (1/2)x+(3/5)=(1/10) | | (7x+2)-(4x-2)= | | 2x^2+x-(1/4)=0 | | (1/2)x=(11/14)x+(4/7) | | x-(x*0.12)=6000 | | 2x^2+x-1/4=0 | | 4b-2=-2 | | .5(4x+2)x=36 | | z/6=-13 | | (2+3x/7)+(3-x/2)=(29/14) | | 5a+2=3a+4 | | y=5+2(3+4) | | 7x+4-6x=0 | | -6=-6y | | 8p+5=7p+10 | | (1/5)(x-4)=3x-2(x-1)+(66/5) | | 9k=8 |